Science high schools and their graduates' career decisions perspectives for educational policy formulation - Alto, Romulita Cabanos 1942- (1983)
This follow-up study is designed to determine the relationship of school- and some person-related variables to the career choice of 404 graduates of the Philippines Science High School, Manila Science High School and Quezon City Science High School and 43 non-science high school graduates who opted for science and mathematics courses. Sex was found to be associated with career choice for science and mathematics courses; perceived socio-economic status and career choice are significantly related. Variation in career choice was determined by school-related variables, namely: curriculum, school practices and faculty and by only one person-related variable, interest for science
Thesis (D.Ed.)--University of the Philippines, Diliman.
Keywords: High school graduates -- Philippines -- Manila metropolitan area; Vocational guidance -- Philippines -- Manila metropolitan area